Impulsive functional differential equations of fractional order with variable moments - Ergören, H. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We establish some existence results for the solutions of initial-value problems for fractional-order impulsive functionaldifferential equations with neutral-delay at variable moments.